2015
DOI: 10.4103/0972-124x.153478
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effects of 0.12% chlorhexidine and herbal oral rinse on dental plaque-induced gingivitis: A randomized clinical trial

Abstract: Background:Chlorhexidine (CHX) is considered as a gold standard of antimicrobial rinses. Various herbal oral rinses are available in the market. However, little is known of its effectiveness.Aim:The aim of this study was to evaluate the clinical changes after the usage of herbal oral rinse and 0.12% CHX.Materials and Methods:In a randomized clinical trial, 76 patients with dental plaque-induced gingivitis were assigned to Group I (Herbal Oral Rinse - Hiora®) and 76 patients with dental plaque-induced gingiviti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…When treated with chlorhexidine, herbal mouthwash, pomegranate peel extract 100%, and pomegranate peel extract 75%; the mean zone of inhibition against S. mutans is 15.92 mm, 30.15 mm, 17.47 mm, and 15.39 mm, respectively, as shown in Table 1 and Graph 1; and against lactobacillus, the mean zone of inhibition of these mouthwashes was 21.94 mm, 24.53 mm, 19.92 mm, and 17.31 mm, respectively, as shown in Table 2 and Graph 2. Herbal mouthwash had demonstrated a significant reduction in S. mutans and lactobacillus count.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…When treated with chlorhexidine, herbal mouthwash, pomegranate peel extract 100%, and pomegranate peel extract 75%; the mean zone of inhibition against S. mutans is 15.92 mm, 30.15 mm, 17.47 mm, and 15.39 mm, respectively, as shown in Table 1 and Graph 1; and against lactobacillus, the mean zone of inhibition of these mouthwashes was 21.94 mm, 24.53 mm, 19.92 mm, and 17.31 mm, respectively, as shown in Table 2 and Graph 2. Herbal mouthwash had demonstrated a significant reduction in S. mutans and lactobacillus count.…”
Section: Resultsmentioning
confidence: 98%
“…Kaim et al suggested that there are certain ingredients in herbal oral rinses that exhibit the evidence of antiinflammatory and antifungal therapeutic effects. [14] …”
Section: Discussionmentioning
confidence: 99%
“…The findings of present study are in accordance with a study by Anup N et al, 12 who also demonstrated the efficacy of Hiora in reducing the plaque. Studies by Narayan A et al 13 & Bhate D et al 14 have also reported the efficacy of Hiora as a plaque reducing agent. In contrast to present study, Southern EN et al 15 have demonstrated Hiora to be ineffective compared to a placebo in relation to plaque reduction.…”
Section: Discussionmentioning
confidence: 97%
“…4 Chlorhexidine has undesirable side effects, and one of the most common is staining of teeth. 5 Herbal mouthwashes are gaining popularity due to reduced side effects, 6 hence, there has been increased interest in plants with antibacterial and antiinflammatory activities. 7 One of the numerous herbal extracts, Green tea (Camellia sinensis) has numerous medicinal benefits, mainly due to its antibacterial and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%